Augmented Criticism, Extensible Archives, and the Progress of Renaissance Studies - Ullyot, Michael (Renaissance and Reformation / Renaissance et Réforme, 2014)
In the three decades since the rise of New Historicism, Renaissance studies has progressed through extensions of scholars’ archival reach to new objects for new interpretations. The future will bring expansions on a larger scale, like those we now witness in English print archives. Machine-readable transcriptions of some fifty thousand texts now enable scholars to use algorithms that tell us things about them that are true, yet can only be known in the future. This is an argument not for an algorithmic criticism but for an augmented criticism, in which human judgments are the origin and outcome of algorithmic research methods. It sketches the emergent methods that are possible only in 2015, yet will do for the archival humanities what telescopes did for astronomy.